Characterizing a syntactic pattern of formgiving in design thinking process / Rusmadiah Anwar - Anwar, Rusmadiah (Institute of Graduate Studies, UiTM, 2017)
Design in a creative way involves a high degree of enigmatic and mystery especially at the early stage of a project. On the whole, conventional industrial design investigation faced with numerous of dilemma especially on the design methodology. The unclear design approach practiced among the creative designers comes to the technical hitches to introduce a new product design. The challenge of current trends in design research and point out some of their activities, such as the gap between aesthetic and technical need, and the chasm between ambiguous and quantified in design practice. In line with the awareness of high-quality aesthetic appeal in industrial product development, therefore, exist a need to revamp this uncertainty design activity (form structuring) for more accurate and being understood during the decision-making in product synthesis. This need together with the enhanced understanding and ability to handle visual product form, necessitate structuring throughout the creative process. In order to deal with these problems, it is recommended to develop a research guideline on the observation setup procedure. These promises to improve the ecological validity over the empirical design research methodology include the possible sampling required. The main goal of the analyzes is to formulate a methodology for analyzing qualitative data in an objective way. The design practice was analyzed through empirical design studies to uncover the design thinking approaches and their standpoint on design solutions throughout formgiving process…